2016
DOI: 10.1177/0160017616672516
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity in Amenity and Labor Market Migration

Abstract: The disequilibrium and equilibrium models of migration disagree on how local amenities and labor market dynamics influence regional in-migration. Research into migration motives and decision-making show that migration for some individuals is mainly driven by proximity to the labor market, while migration for others is mainly amenity driven. As this is an ongoing process, it should result in a spatial sorting based on migration motives. This means that global models explaining in-migration underestimate the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Using data from Germany and Sweden, Arntz (2010) and Niedomysl and Hansen (2010) also supported the predominance of job considerations. Using data from the Netherlands, Rijnks, Koster, and McCann (2018) emphasized that there exists spatial heterogeneity in that the impacts of amenities on migration vary across regions. Focusing on the migration of households displaced by violent conflicts in Colombia, Lozano-Gracia et al (2010) find that more populated regions are more attractive as they provide a sufficient level of fulfillment of basic needs.…”
mentioning
confidence: 99%
“…Using data from Germany and Sweden, Arntz (2010) and Niedomysl and Hansen (2010) also supported the predominance of job considerations. Using data from the Netherlands, Rijnks, Koster, and McCann (2018) emphasized that there exists spatial heterogeneity in that the impacts of amenities on migration vary across regions. Focusing on the migration of households displaced by violent conflicts in Colombia, Lozano-Gracia et al (2010) find that more populated regions are more attractive as they provide a sufficient level of fulfillment of basic needs.…”
mentioning
confidence: 99%
“…Recent developments in research on spatial heterogeneity suggest that both the correlation between local amenities and desirability of the location (noted in Rijnks et al (2018)) and the correlation between property characteristics and desirability of the property (discussed in Helbich et al (2013)) might be spatially non-stationary. This spatial non-stationarity of the coefficients most likely results from an omitted spatial variable interacting with the variables of interest, as discussed in Billé et al (2017).…”
Section: Hedonic Analysis With Unmeasured Attributesmentioning
confidence: 99%
“…Storper and Scott (2009) suggested that the compensation effect of amenities for insufficient economic opportunities was exaggerated. Some scholars consider both factors as relevant (Royuela et al., 2010; Rodriguez-Pose and Ketterer, 2012; Yang et al., 2017; Rijnks et al., 2018). In a word, the evidence on the role of economic opportunities and amenities in migration is insufficient and/or mixed.…”
Section: Literature Reviewmentioning
confidence: 99%